2013
DOI: 10.4244/eijv9i8a165
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of the relationship between shear stress and necrotic core in early and advanced coronary artery disease

Abstract: With the advancement of disease, necrotic core is less often located at low WSS regions, but exposed to high WSS, which is probably the result of lumen narrowing. Necrotic core in contact with the lumen was most frequently exposed to high WSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 23 publications
3
34
0
1
Order By: Relevance
“…ESS has been implicated in atherosclerosis development and progression [6] and is correlated with high risk plaque characteristics [8]. Key to its estimation is the coronary artery lumen 3D model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESS has been implicated in atherosclerosis development and progression [6] and is correlated with high risk plaque characteristics [8]. Key to its estimation is the coronary artery lumen 3D model.…”
Section: Discussionmentioning
confidence: 99%
“…Low ESS is an independent predictor of increased plaque burden, plaque progression and luminal narrowing in both animals [3-5] and humans [6, 7]. Conversely, high ESS has been associated with plaque transition to an unstable phenotype [6] and with high risk plaque characteristics [8]. Autopsy [9] and clinical [10] studies have also shown that the majority of high-risk plaques occur in the proximal portions of the major coronary arteries [11-13].…”
Section: Introductionmentioning
confidence: 99%
“…In the carotid circulation, ulceration of carotid plaques, visible on angiography or on pathological examination, was seen most often in regions where WSS was highest [43] and the inflammatory burden was severe [44]. In line with the experimental and autopsy studies, longitudinal and cross-sectional human coronary and carotid studies have shown an increase in plaque necrotic core, calcium [35], and strain [45], development of expansive remodeling [35,46], presence of IPH [47], large necrotic core [34,46,48], a necrotic core in contact with the lumen [48], and napkin-ring sign [46] in areas exposed to high WSS. Meanwhile, some data show that WSS might not have the same role in development of plaque erosion as it has in the development of plaque rupture [9,10].…”
Section: High Wall Shear Stressmentioning
confidence: 96%
“…progression and rupture (1,17). The complete scaffold integration into the vascular wall has shaped a neoplaque phenotype that resulted from the complex interaction of pre-existing plaque, morphological changes of the pre-existing plaque subject to dynamic local rheological factors (18,19), strut resorption, and neointima formation (8). We visually characterized neoplaque using standardized OCT criteria (7).…”
Section: Figure 2 Quantifying Signal-rich Layer Thickness In Differenmentioning
confidence: 99%